Pharmacokinetic profiles of the active metamizole metabolites in healthy horses. Issue 2 (31st July 2016) - Giorgi, M.; Aupanun, S.; Lee, H.‐K.; Poapolathep, A.; Rychshanova, R.; Vullo, C.; Faillace, V.; Laus, F.
Abstract : Metamizole (MT) is an analgesic and antipyretic drug labelled for use in humans, horses, cattle, swine and dogs. MT is rapidly hydrolysed to the active primary metabolite 4‐methylaminoantipyrine (MAA). MAA is formed in much larger amounts compared with other minor metabolites. Among the other secondary metabolites, 4‐aminoantipyrine (AA) is also relatively active. The aim of this research was to evaluate the pharmacokinetic profiles of MAA and AA after dose of 25 mg/kg MT by intravenous (i.v.) and intramuscular (i.m.) routes in healthy horses. Six horses were randomly allocated to two equally sized treatment groups according to a 2 × 2 crossover study design. Blood was collected at predetermined times within 24 h, and plasma was analysed by a validated HPLC‐UV method. No behavioural changes or alterations in health parameters were observed in the i.v. or i.m. groups of animals during or after (up to 7 days) drug administration. Plasma concentrations of MAA after i.v. and i.m. administrations of MT were detectable from 5 min to 10 h in all the horses. Plasma concentrations of AA were detectable in the same range of time, but in smaller amounts. Maximum concentration ( C max ), time to maximum concentration ( T max ) and AUMC0‐last of MAA were statistically different between the i.v. and i.m. groups. The AUCIM /AUCIV ratio of MAA was 1.06. In contrast, AUC0‐last of AA was statistically different between the groups ( P  <   0.05) with an AUCIM /AUCIV ratio of 0.54. This study suggested that the differences in the MAA and AA plasma concentrations found after i.m. and i.v. administrations of MT might have minor consequences on the pharmacodynamics of the drug.